Effect of temperature on performance of Boron Trifluoride (BF3) gas-based neutron proportional counters. (June 2021) - Desai, Shraddha S.; Rao, Mala N.
Abstract: Experimental facilities with a requirement of large neutron detection area, prefer gas filled detectors over all other detector technologies. Scarcity and exorbitant cost of 3 He, have made the development of large neutron detector banks a tough challenge. BF3 is a substitute for 3 He gas in proportional counters with advantage of high gamma tolerance and cost effectiveness. Its lower efficiency can be compensated by using an array of detectors. Neutron detectors mounted at various outdoor experimental facilities experience the atmospheric temperature variation from −10 °C to 50 °C. Pulse height distribution of the BF3 filled detectors vary considerably with operating temperature. Performance of the BF3 gas filled neutron detectors within the temperature range of interest were investigated. Gas gain characteristics and Diethorn gas constants indicate the microscopic effect of anode bias on avalanche formation. The variation of these parameters for BF3 gas with respect to temperature were evaluated. These gas constants are useful to design the detectors and estimate operating parameters for any anode-cathode complex geometry. The deviation in efficiency and sensitivity of the neutron detector with temperature was evaluated. The data obtained is useful to apply corrections during precision experiments involving temperature variation. Highlights: To study performance of the BF3 gas filled Neutron detectors aimed at various outdoor experimental facilities. To measure Gas gain characteristics and Diethorn gas constants of BF3 gas within the temperature range of interest. To evaluate deviation in efficiency and sensitivity of the neutron detector with temperature. To optimize the detector design to enhance the performance and life of the detector.